Pengembangan Bahan Ajar Berbasis Canva untuk Meningkatkan Kemampuan Menulis dan Mengkomunikasikan Cerita Pendek - Zahrotul Aliyah Ulfayati; Mustaji; Siti Aisyah (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
Writing and communicating short stories is an essential skill that elementary school students should develop to enhance their imagination. Unfortunately, this ability still receives relatively little attention, mainly due to factors such as the limited availability of teaching materials and the less interactive learning process. In fact, the development of digital technology, such as Canva, can be used to create teaching materials that are more interactive and fuller of visuals. This research aims to develop teaching materials that are valid, practical, and effective in improving the ability to write and communicate short stories among 5th-grade elementary school students. This research employs a combined method, utilizing the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model to develop new teaching materials. The subjects of this study are 21 students from Class V B at Madrasah Ibtidaiyah Masjid Al Akbar Surabaya. Data collection was carried out through interviews, observations, documentation, pre-test and post-test sheets, and questionnaires. Data analysis was conducted using a paired sample t-test with the help of the SPSS version 26 application. The results showed that the Canva-based teaching materials developed were valid, as validated by three experts, practical, based on questionnaires completed by Indonesian teachers, and effective, as indicated by the increase in scores between the pre-test and post-test in writing and communicating short stories. There was an increase in the average score between pre-test and post-test of 18.81 points in the ability to write short stories and an increase in the value of 15.24 in the ability to communicate short stories. This is strengthened from the analysis with the help of SPSS version 26, showing a significant result of 0.000, which is smaller than 0.05 and confirms the difference in results between pre-test and post-test.